2013
DOI: 10.1210/en.2013-1086
|View full text |Cite
|
Sign up to set email alerts
|

Yolk Formation in a Stony Coral Euphyllia ancora (Cnidaria, Anthozoa): Insight Into the Evolution of Vitellogenesis in Nonbilaterian Animals

Abstract: Vitellogenin (Vg) is a major yolk protein precursor in numerous oviparous animals. Numerous studies in bilateral oviparous animals have shown that Vg sequences are conserved across taxa and that Vgs are synthesized by somatic-cell lineages, transported to and accumulated in oocytes, and eventually used for supporting embryogenesis. In nonbilateral animals (Polifera, Cnidaria, and Ctenophora), which are regarded as evolutionarily primitive, although Vg cDNA has been identified in 2 coral species from Cnidaria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 44 publications
4
67
0
Order By: Relevance
“…However, few studies have examined the characteristics and function of gonadal somatic cells in corals. Previously, the authors of the present study have found that several types of yolk proteins are produced by the ovarian somatic cells adjacent to oocytes and are then transported to and accumulate in oocytes during oogenesis in the stony coral Euphyllia ancora (Shikina, Chiu, Lee, & Chang, 2015;Shikina et al, 2013). These findings clearly demonstrate that gonadal somatic cells are specialized to support oocyte development and play a crucial role in coral oogenesis.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…However, few studies have examined the characteristics and function of gonadal somatic cells in corals. Previously, the authors of the present study have found that several types of yolk proteins are produced by the ovarian somatic cells adjacent to oocytes and are then transported to and accumulate in oocytes during oogenesis in the stony coral Euphyllia ancora (Shikina, Chiu, Lee, & Chang, 2015;Shikina et al, 2013). These findings clearly demonstrate that gonadal somatic cells are specialized to support oocyte development and play a crucial role in coral oogenesis.…”
supporting
confidence: 72%
“…Characteristic differences in somatic tissues/cells between males and females remain unclear. Our previous study has demonstrated that yolk protein synthesis occurs in ovarian somatic cells in E. ancora , and the expression of these yolk proteins is rarely detected in testicular cells (Shikina et al, , Shikina, Chung et al, ). The present study immunohistochemically demonstrated that the expression of GFP is mainly observed in the testicular somatic cells, with lower expression in ovarian somatic cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although VTG is suggested to be synthesized by somatic cells in the putative ovarian tissue of the coral Euphyllia ancora , a diploblast cnidarian considered to be a long divergent branch of metazoans (Shikina et al, ), our present report of VTG expression solely in ovarian tissue, without transport by hemolymph, is unique; in other invertebrates, such as crustaceans, VTG is synthesized in the hepatopancreas and ovary (Subramoniam, ), while in insects it is synthesized in the fat body (Tufail et al, ) and in nematodes it is reportedly produced in the intestine (Wahli, ). Ovary‐specific expression of VTG was reported in the abalone (Matsumoto, Yamano, Kitamura, & Hara, ) and the oyster (Matsumoto, Nakamura, Mori, & Kayano, ; Ni et al, ), which are species belonging to the same molluscan group as cephalopods.…”
Section: Discussionmentioning
confidence: 54%
“…Gonad isolation not only requires an understanding of polyp anatomy, but also technical skill. The present study applied previously established techniques for gonad isolation from E. ancora polyps [12] to the current transcriptomic study. Bioinformatics methods to eliminate contigs from symbiotic dino agellates or other contaminants were also employed [31].…”
Section: Scleractinian Gonadal Transcriptome Assemblymentioning
confidence: 99%